The Role of Zinc-Rich Food Consumption on Zinc Level and the Incident of Preeclampsia - Harvey Alvin Hartono; Efendi Lukas; Nasrudin Andi Mappaware; Maisuri Tadjuddin Chalid; Andi Mardiah Tahir; Isharyah Sunarno (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2023)
Objective: Investigate the correlation between dietary intake of zinc, preeclampsia and blood zinc levels. Methods: This study, which compared pregnant women in the third trimester at the Wahidin Sudirohusodo Hospital and the educational network hospital with and without preeclampsia, used a Cross Sectional methodology. Zinc level testing was carried out at Prodia using ICP-MS method. Mann Whitney, Kruskal Wallis, and chi square tests were used to examine the data.Results: Preeclampsia group (n=38) and control group (n=40) were two groups made up of a total of 78 pregnant women. Zn level of severe preeclampsia (47.73 ± 11.23 ng/mL) was lower than preeclampsia (50.50 ± 13.59 ng/mL) and non-preeclampsia (50.58 ± 10.12ng/mL), but not significantly. Lower zinc rich-food consumption was a significant effect on zinc deficiency (p< 0.05), and was no significant effect on preeclampsia (p > 0.05).Conclusion: Low intake of zinc-rich foods and occasionally exposure to cigarette smoke are the causes of zinc insufficiency in third trimester pregnancy, but has little impact on the occurrence of preeclampsia.Peranan Konsumsi Makanan Kaya Zink terhadap Kadar Zink dan Insiden PreeklamsiaAbstrak Tujuan: Mengetahui korelasi antara asupan zink, preeklamsia dan tingkat zink serum.Metode: Penelitian ini membandingkan ibu hamil trimester III di RS Wahidin Sudirohusodo dan RS jejaring pendidikan dengan dan tanpa preeklampsia menggunakan metodologi Cross Sectional. Pengujian kadar zink dilakukan di Prodia dengan menggunakan metode ICP-MS. Uji Mann Whitney, Kruskal Wallis dan Chi Square digunakan untuk menganalisis data. Hasil: Kelompok preeklamsia (n=38) dan kelompok kontrol (n=40) adalah dua kelompok yang terdiri dari total 78 ibu hamil. Kadar Zn preeklamsia berat (47.73 ± 11.23 ng/mL) lebih rendah dibandingkan preeklamsia (50.50 ± 13.59 ng/mL) dan non preeklamsia (50.58 ± 10.12ng/mL), tetapi tidak bermakna. Rendahnya konsumsi makanan kaya zink berpengaruh signifikan terhadap defisiensi zink (p<0.05), namun tidak signifikan terhadap kejadian preeklamsia (p>0.05). Kesimpulan: Diet rendah zink dan paparan asap rokok adalah penyebab defisiensi zink pada kehamilan trimester III, tetapi memiliki dampak kecil terhadap insiden preeklamsia.Kata kunci: preeklamsia, kehamilan, zink